2013
DOI: 10.1080/09712119.2012.738222
|View full text |Cite
|
Sign up to set email alerts
|

Repair of abdominal wall hernias using acellular dermal matrix in goats

Abstract: The present study was undertaken to evaluate the efficacy of acellular dermal matrix (ADM) of caprine origin for the repair of abdominal wall hernias in six goats. The skin of goat was de-epithelialised using a 2 M sodium chloride solution and 0.25% trypsin, and further decellularised using 2% sodium deoxycholate, which was then used as graft material. Under xylazine sedation and local infiltration analgesia, the abdominal wall hernias were repaired with ADM graft using inlay graft technique. All animals had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…These results were in accordance with Kumar et al . (2012, 2013a,b,c). Recurrence of the hernia is a relatively common complication of herniorrhaphy and has been reported after repair using sutures alone (Cook et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in accordance with Kumar et al . (2012, 2013a,b,c). Recurrence of the hernia is a relatively common complication of herniorrhaphy and has been reported after repair using sutures alone (Cook et al .…”
Section: Discussionmentioning
confidence: 99%
“…2012; Kumar et al . 2013a,b,c). The potential benefits of biological materials include improved infection resistance, host tissue ingrowth and less adhesion formation (Gaertner et al .…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular matrix (ECM) scaffolds primarily composed of structural collagen protein are widely used in tissue engineering and regenerative medicine [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These are usually prepared from animal tissues by decellularization process.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic techniques of decellularization include the use of protease (trypsin) [1-5, 8, 10, 12-15], endonucleases and exonucleases. Chemical methods of decellularization include the use of acids and alkalis (acetic acid, peracetic acid, hydrochloric acid, sulfuric acid, ammonium hydroxide), nonionic detergents (Triton X-100), ionic detergents (sodium dodecyl sulfate, sodium deoxycholate, Triton X-200) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], zwitterionic detergents (3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate, sulfobetaine-10, sulfobetaine-16), organic solvent (Tri(n-butyl)phosphate) [3,10], hypertonic and hypotonic solutions [2,3,8,10,13,15], and chelating agents (EDTA). These reagents at higher concentrations extensively disrupt the structural proteins of ECM scaffolds and make it impossible to analyze by routine techniques [17].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Several studies reported that ADM grafts have been used for the reconstruction of abdominal wall defects in rabbits, rats, goats, and humans. [24][25][26][27] Although the results of the studies were promising, the personalized reconstruction of the ADM as needed is limited, and the cost is very high. In addition, to our knowledge, there is no research on using ADM powder to reconstruct abdominal wall defects.…”
Section: Introductionmentioning
confidence: 99%